Key Drivers for the Light Duty Truck Owners in Purchase of Electric Vehicles - Tuares, Mary May Cejar (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the key drivers influencing the purchase decisions of electric vehicles (EVs) among light-duty truck owners in the National Capital Region (NCR), Philippines, in support of sustainable transportation and business practices. With the increasing urgency for eco-friendly logistics and the enforcement of the Electric Vehicle Industry Development Act (EVIDA), this research aims to identify the primary considerations of truck-owning businesses transitioning to EVs. Specifically, it seeks to assess how sustainability, technology acceptance, government programs, and business needs and operations impact the purchasing behavior of fleet owners. Employing a descriptive quantitative research design, the study surveyed 151 business owners and fleet managers using stratified random sampling. Data was collected via online questionnaires and statistically analyzed using mean, standard deviation, percentage, ranking, and Analysis of Variance (ANOVA). These tools were used to identify patterns and test the significance of differences in purchase considerations across demographic groups such as business revenue, size, and years in operation. Findings revealed that all four key drivers were rated with “Very High Influence,” with business needs and operations—particularly vehicle durability, lifespan, and operational efficiency—ranking as the most influential. ANOVA results showed significant relationships between business revenue and the major drivers, confirming that financial capability and company experience strongly shape EV purchasing decisions. The study concludes with actionable recommendations for policymakers, automotive manufacturers, and stakeholders to design marketing strategies and incentive programs that align with operational and sustainability needs in NCR’s commercial vehicle sector.